Recent advances in near-infrared photobiomodulation for the intervention of acquired brain injury - Yujing Huang; Yujing Zhang; Chen Yang; Mengze Xu; Zhen Yuan (Journal of Innovative Optical Health Sciences)
Acquired brain injury (ABI) is an injury that affects the brain structure and function. Traditional ABI treatment strategies, including medications and rehabilitation therapy, exhibit their ability to improve its impairments in cognition, emotion, and physical activity. Recently, near-infrared (NIR) photobiomodulation (PBM) has emerged as a promising physical intervention method for ABI, demonstrating that low-level light therapy can modulate cellular metabolic processes, reduce the inflammation and reactive oxygen species of ABI microenvironments, and promote neural repair and regeneration. Preclinical studies using ABI models have been carried out, revealing the potential of PBM in promoting brain injury recovery although its clinical application is still in its early stages. In this review, we first inspected the possible physical and biological mechanisms of NIR-PBM, and then reported the pathophysiology and physiology of ABI underlying NIR-PBM intervention. Therefore, the potential of NIR-PBM as a therapeutic intervention in ABI was demonstrated and it is also expected that further work can facilitate its clinical applications.